Ichthyofauna of Gibe Sheleko National Park and some morphometric relationships of fish of the tributary rivers, Southern Ethiopia - Mekonen, Sefi; Hailu, Abera (Journal of Fisheries, 2021)
Understanding of Ichthyofaunal diversity is a major gateway for the conservation of waterbodies in the world. Ethiopia has a rich Ichthyofaunal diversity, although they are poorly known. This study was carried out in two tributary rivers (Gibe and Wabe) of Gibe Sheleko National Park to investigate Ichthyofaunal diversity and morphometric characteristics of fish. By using monofilament gill-nets, fish were collected, identified and measured their morphometric. A total of 10 species were identified, dominated by Synodontis schall, followed by Labeobarbus nedgia and Labeobarbus intermedius. According to the Index of Relative Importance, S. schall was also first (49.13%), followed by L. intermedius (15.49%). Gibe River had a higher number of species than Wabe River. The Shannon Diversity Index in Gibe River was also higher (2.09) than Wabe (1.84) during the dry season, but lowest in the wet season (1.52 and 1.57 respectively). Synodontis schall had the largest girth, but Clarias gariepinus had the largest eye diameter and body weight. Heterobranchus longifilis was first in total, fork and standard body length. Generally, differences in sampling habitats and fishing effort might have contributed to discovered variants findings. Fishery development should be implemented in the Park to use the fish resource sustainably.